Social entrepreneurship ecosystem: The case of the state of Paraíba (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This article aims to analyze the configurations of the Social Entrepreneurship Ecosystem (SEE) in Paraíba from the model described by Isenberg (2011) adapted by Audretsch et al. (2022). The case study had a qualitative approach of a descriptive and exploratory nature. The techniques were non-participant observation and semi-structured interviews. The units of analysis were the actors involved in the SEE of Paraíba. The SEE brings together a set of talents with transformative potential. However, the main challenges encountered are the lack of public policies and training. With this, the SEE of Paraíba proved to be an environment still in development, lacking interaction between the actors for the ecosystem strengthening of the region.